Dr Józef Morawiec (1927-2017) - CZYŻ, Henryka (Archives of Acoustics, 2017)
Dr Józef Morawiec, retired lecturer at the Pedagogical University in Rzeszów (1966–1992), co-founder of its Department of Physics, a founder-member of the Rzeszów Branch of the Polish Acoustics Associations, passed away on April 20, 2017.